Socio-Economic Impacts of the COVID-19 Pandemic: The Case of Bandung City - Encup Supriatna (Journal of Governance, 2020)
The COVID-19 pandemic has had a wide impact on various sectors of people's lives, including the social and economic sectors. This study aims to analyze the social and economic impacts caused by the COVID-19 pandemic, by taking a case study in the city of Bandung. This research was conducted using qualitative methods with data collection techniques such as observation, interviews, and documentation studies. The results of this study found that the COVID-19 pandemic harmed the economy of the people of Bandung because many were unemployed and many became new poor citizens. While from the social aspect, a prolonged COVID-19 pandemic will lead to potential conflicts if the basic needs of the community are not met properly. The implication is that the Bandung City Government needs to expand its social protection program to help the poor, both new and existing ones. But the positive aspect of this pandemic is that it raises the collective awareness of the community to help each other, thus creating social solidarity among the people.